2018
DOI: 10.9794/jspccs.34.182
|View full text |Cite
|
Sign up to set email alerts
|

Transition of Aortopulmonary Collateral Arteries before and after the Fontan Procedure

Abstract: Background:In patients with a functional single-ventricle, coil embolization is commonly performed to avoid complications after the Fontan procedure. The position for coil embolization should be determined after considering the postoperative changes in the aortopulmonary collateral arteries (APCAs). Methods:The study involved 163 patients who underwent the Fontan procedure between 2009 and 2015. The amount of APCA was assessed using a 3-point scale based on the aortogram in the cardiac catheterization. The tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, we routinely provided home oxygen therapy soon after the bidirectional Glenn operation based on the clinical implication that oxygen might have favorable effects on the bidirectional Glenn circulation by suppressing the sympathetic tone and lowering pulmonary vascular resistance. 9) Protocol of the APC coil embolization: We evaluated the amount of APC based on an aortogram 10) and instantly discussed the necessity for coil embolization in each case. Although there are no definite criteria for performing coil embolization, we typically perform it in cases where APCs are so significant that there are apparent overloads to the main ventricles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we routinely provided home oxygen therapy soon after the bidirectional Glenn operation based on the clinical implication that oxygen might have favorable effects on the bidirectional Glenn circulation by suppressing the sympathetic tone and lowering pulmonary vascular resistance. 9) Protocol of the APC coil embolization: We evaluated the amount of APC based on an aortogram 10) and instantly discussed the necessity for coil embolization in each case. Although there are no definite criteria for performing coil embolization, we typically perform it in cases where APCs are so significant that there are apparent overloads to the main ventricles.…”
Section: Methodsmentioning
confidence: 99%
“…A previous report from our institute demonstrated that significant APC either does not emerge or its amount declines after the Fontan operation. 10) From this report, we considered that routine APC coil embolization was not necessary. Considering that APC can resolve after a Fontan opera-RISK FACTORS AND EFFECT OF APC COIL EMBOLIZATION tion, the main purpose of embolization is to achieve a favorable Fontan circulation.…”
Section: The Effect Of Apc Coil Embolization On Adaptation Tomentioning
confidence: 96%
See 1 more Smart Citation